(untitled) (Bangladesh Journal of Urology, 2023)
Background: Treatment of renal stone is a common practice in urology. A total of four minimally invasive therapy options, including ESWL (Extracorporeal shock wave lithotripsy), PCNL (Percutaneous nephrolithotomy), RIRS (retrograde intrarenal stone surgery), and LSS (laparoscopic stone surgery), are now available for the treatment of kidney stones. PCNL is the gold standard for large renal stones. The prone position for doing PCNL is the standard of teaching and used by most of the urologists. Supine positioning for PCNL is also another well-established method but urologists do not frequently use it due to unfamiliarity with the positioning and puncturing technique under fluoroscopic guidance. The objective of the current study was to evaluate the safety and effectiveness of supine PCNL for the treatment of big renal stones and paying close attention to the complications. Methods: This study was a prospective cross sectional study which was conducted at the department of Urology in Mugda Medical College Hospital & some private hospital in Dhaka. The study was conducted during the period of January 2020- December 2021. The total sample size for this study was 84. Result: The mean age of the patients was 39.7 ±15. Most of the patients 48(57.1%) were male and 36(42.9%) were female. Mean BMI, kg/m2 was 25.2 ±6.9 and mean Stone burden (mm) was 29.9 ±10.9. Most of the stone 44(52%) were on right side and 40(48%) were on left side. Radio-opaque was seen in 58(69%) cases, Radiolucent in 17(20.2%) and mixed in 9(10.7%) cases. Mean time for initial puncture was 12.24±5.19, mean intraoperative period (in minutes) was 52.42 ±10.28, mean haemoglobin drop (gm/dl) was 0.91 ±0.51, mean duration of hospital stay (post-operative in days) was 3.2 ±1.7, auxiliary procedure were required in 4 cases. The stone free rate was 80(95.2%). Conclusion: Supine PCNL can be used to treat all stone sizes and is technically viable. It also has a number of potential benefits, particularly for individuals who are obese and at high risk when under anaesthesia or where simultaneous use of ureterorenoscopy (URS) is needed. Bangladesh J. Urol. 2023; 26(2):64-69